HLA-DQ Allele Carriers as Genetic Risk Factors for Pulmonary Tuberculosis: A Meta-Analysis - Talarima, Bellytra; Amiruddin, Ridwan; Daud, Nurpudji Astuti; Noor, Nur Nasry; Massi, Muhammad Nasrum; Saleh, Lalu Muhammad (International Journal of Statistics in Medical Research, 2026)
Several studies have shown that pulmonary tuberculosis (PTB) is a major global health issue, affecting various countries around the world. Susceptibility to the disease has been reported to be influenced by host genetic variables, including Human Leukocyte Antigen (HLA) class II genes, specifically HLA-DQ. Despite the association, studies on the relationship between HLA-DQ allele carriers and the risk of PTB are still not consistent among various populations. This meta-analysis aims to assess the association between carrier status (phenotype frequency) of HLA-DQA1 and HLA-DQB1 alleles and susceptibility to pulmonary tuberculosis. Several HLA-DQ alleles were examined, and the pooled effect size estimates were calculated based on carrier (phenotype) frequencies of HLA-DQA1 and HLA-DQB1 alleles, using odds ratios (ORs) and 95% confidence intervals (CI). A total of 21 high-quality studies (NOS ≥7) were included in the review, with 25,896 controls and 3,927 cases. The results showed that the risk of PTB was significantly increased by allele carriers of HLA-DQA1*01:01 (OR = 1.79; 95% CI: 1.22–2.62) and HLA-DQA1*03:01 (OR = 1.64; 95% CI: 1.08–2.48). Risk factors for HLA-DQB1 allele carriers were also found to be the *02:01 (OR = 1.36; 95% CI: 1.04–1.79), *05:03 (OR = 1.35; 95% CI: 1.01–1.80), and *06:01 (OR = 1.41; 95% CI: 1.00–1.97) allele carriers. Meanwhile, HLA-DQA1*02:01, *04:01, *05:01, and *06:01 allele carriers had protective effects. The majority of analyses found no indications of publication bias. This meta-analysis demonstrates that carrier status of specific HLA-DQA1 and HLA-DQB1 alleles is significantly associated with susceptibility to pulmonary tuberculosis